2014
DOI: 10.1007/s11552-014-9628-8
|View full text |Cite
|
Sign up to set email alerts
|

Digit Replantation in Children: A Nationwide Analysis of Outcomes and Trends of 455 Pediatric Patients

Abstract: The rate of pediatric replantation has been relatively low, being 27 % at most in a given year. Importantly, short-term outcomes are better in children than for adults, supporting the indication to perform replantation in this age group when the surgeon feels that replantation is feasible and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 30 publications
(49 reference statements)
0
27
0
Order By: Relevance
“…Statistical analysis revealed that the following variables failed to influence replant survival: age, sex, zone of injury, digit number, tobacco use, ischemia time, method of preservation, and use of vein graft. The authors found that 19 studies evaluated the role of sex and survival, 4,12,13,[15][16][17][20][21][22]24,25,[27][28][29][30]32,34,35,37 13 studies evaluated the zone of injury, 13,[15][16][17][18]21,23,26,27,33,34,36,38 15 studies evaluated digit number, 4,13,15,17,[20][21][22]24,29,32,33,35,[39][40][41] 5 studies evaluated tobacco use, 4,13,…”
Section: Resultsmentioning
confidence: 99%
“…Statistical analysis revealed that the following variables failed to influence replant survival: age, sex, zone of injury, digit number, tobacco use, ischemia time, method of preservation, and use of vein graft. The authors found that 19 studies evaluated the role of sex and survival, 4,12,13,[15][16][17][20][21][22]24,25,[27][28][29][30]32,34,35,37 13 studies evaluated the zone of injury, 13,[15][16][17][18]21,23,26,27,33,34,36,38 15 studies evaluated digit number, 4,13,15,17,[20][21][22]24,29,32,33,35,[39][40][41] 5 studies evaluated tobacco use, 4,13,…”
Section: Resultsmentioning
confidence: 99%
“…Variables considered as candidates for a treatment decision rule ( Downloaded From: https://jamanetwork.com/ on 09/12/2020 amputation, dominant hand injury, amputation level, mechanism of injury, and bilateral injury because these factors are clinically relevant to decision-making. 7,9,12,13,23,24 In addition to these candidate variables, possible confounding variables included in the propensity model included sex, race/ethnicity, educational level, income level, marital status, employment status, occupation group, location of care, work-related injury, insurance, and insurance type.…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…To date, the literature provides variable conclusions regarding outcomes in children versus adult replants. 6,39 As such, we elected to include data on children in our analysis. Due to limitations in data reporting, we were unable to determine whether the chosen modality for replant revision (i.e., nonsurgical management) was influenced by the use of vein grafts during the index procedure, lack of identifiable veins available for anastomosis, or lack of distal vein targets.…”
Section: Discussionmentioning
confidence: 99%